2006
DOI: 10.1590/s1516-35982006000100024
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento e desempenho reprodutivo de novilhas Nelore criadas a pasto nos cerrados do Centro-Oeste brasileiro

Abstract: RESUMO -Foi simulado e validado um modelo de cria e recria a pasto de fêmeas Nelore nos cerrados do Centro-Oeste brasileiro. Foram determinados os ganhos de peso médios diários (GMD) durante três anos: na primeira seca após a desmama, em pastagem de Brachiaria brizantha (Hochst) Stapf., no período das águas e na segunda seca, em pastagem de Panicum maximum cv. Tanzânia. Os GMD foram: 0,020; 0,550 e 0,172 kg, respectivamente. No segundo período das águas, fase de cria, as novilhas pastejaram em Brachiaria decum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
18

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 10 publications
0
7
0
18
Order By: Relevance
“…Por outro lado, nas bezerras do desmame convencional, ocorreu aumento praticamente linear no GMD (0,516; 0,704 e 1,040 kg, respectivamente). O aumento no GMD das bezerras do desmame convencional ao longo dos anos deve estar associado à mais alta produção de leite das vacas e, embora esta característica não tenha sido avaliada, sabe-se do aumento dessa até a idade adulta da vaca Vieira et al, 2006;Cerdótes et al, 2004b). Outro aspecto pode estar relacionado ao tipo de pastagem, que variou nos três anos durante o período de lactação das bezerras do desmame convencional (Tabela 1), influenciando não apenas na produção de leite das mães, mas também a disponibilidade e a qualidade do pasto para as bezerras.…”
Section: Resultsunclassified
“…Por outro lado, nas bezerras do desmame convencional, ocorreu aumento praticamente linear no GMD (0,516; 0,704 e 1,040 kg, respectivamente). O aumento no GMD das bezerras do desmame convencional ao longo dos anos deve estar associado à mais alta produção de leite das vacas e, embora esta característica não tenha sido avaliada, sabe-se do aumento dessa até a idade adulta da vaca Vieira et al, 2006;Cerdótes et al, 2004b). Outro aspecto pode estar relacionado ao tipo de pastagem, que variou nos três anos durante o período de lactação das bezerras do desmame convencional (Tabela 1), influenciando não apenas na produção de leite das mães, mas também a disponibilidade e a qualidade do pasto para as bezerras.…”
Section: Resultsunclassified
“…Pötter & Lobato (2004) determined calving body weights of 362.5 and 400.9 kg in primiparous Hereford and Braford cows, respectively. Vieira et al (2006) determined in primiparous Nelore cows, an average body weight of 436.0 kg at a date close to calving, during four years of observations. Morrison et al (1999), in a study with multiparous cows presenting moderate body condition score (3-3.5), observed that moderate loss of body reserves in the final third of gestation did not influence subsequent reproductive performance, if forage availability was not limiting to consumption post-calving.…”
Section: Resultsmentioning
confidence: 99%
“…Cows managed exclusively on natural pastures had the lowest final average body weight and body condition score (391.2 kg and 3.41); however, their body condition score was not different (P>0.05) from that of cows submitted to the system of improved pastures pre-calving and natural pastures post-calving (3.50). Wiltbank et al (1962) considered that variations in feeding levels between pre-and post-calving periods have a major effect on reproductive parameters. Pre-calving feeding level significantly influences anoestrus duration, and consequently, the number of cows in the heat in the beginning of the breeding season, with the stronger effects on primiparous than in multiparous cows.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, several authors showed positive correlations between heifer target weight at mating and pregnancy rate (Wiltbank et al, 1985;Silva et al, 2005). Heifers weighing more than 65% of their mature weight, according to breed and type, present high pregnancy rates (Kroetz and Neves, 1985;DeRouen and Franke, 1989), which is an important productivity indicator of breedingto-finish systems (Beretta et al, 2001;Vieira et al 2006).…”
Section: Discussionmentioning
confidence: 99%